Farm-nonfarm linkages in rural Sub-Saharan Africa - Haggblade, Steven; Hazell, Peter B. R.; Brown, James (Elsevier, 1989)
... this paper examines the size and nature of farm-nonfarm linkages in rural Africa. In doing so, it documents the extent, composition, spatial density, and growth patterns of the rural nonfarm economy as well as the policies that are leikely to enhance its role in the development process